INVESTIGATION OF THE POSSIBILITY OF CONVERTING ENVIRONMENTAL HEAT INTO ELECTRICAL ENERGY IN AN OSCILLATORY CIRCUIT CONTAINING A NONLINEAR FERROELECTRIC CERAMIC CAPACITOR - Vladimir Akopyan; Gevorg Karapetyan; Vladimir Kataev; Igor Sysoev; Dmitry Gusev (Вестник Северо-Кавказского федерального университета)
An oscillating circuit is considered, in which a non-linear pyroelectric is used as a capacitor, which is a thin pyroelectric plate. A mathematical model has been developed for the operation of such a circuit based on the solution of the equation together with the equation of forced oscillations in an oscillatory circuit in the linear approximation. The conditions for the parameters of pyroelectric, under which the oscillations in the circuit become continuous and the circuit can be considered as a converter of the heat of the environment into electrical energy, are obtained.